PENGUMPULAN DATA PRODUKTIVITAS TANAMAN PANGAN PADA MASA PANDEMI COVID-19 - Nialita Rahmadhani (Politeknik Statistika STIS, 2020)
The Covid-19 has had an impact not only on the world of health, but also other sectors including the food and agriculture sectors. Food and Agriculture Organization (FAO) regarding the potential of world food scarcity, president Joko Widodo instructed to ensure the availibility of food accurately based on valid data. This is a challenge for BPS to make methodological adjustments so that it can still provide food data, which is crop cutting survey. The purpose of this study is to explain the mitigation and adaptation of the methodology of crop cutting survey, and to provide an evaluation of the impact of these changes. Data used were the subround 1 2019 and Subround 1 2020 of crop cutting survvey collected by BPS and then analyzed using the descriptive method and further analyzed using paired samples t-test analysis. The results showed that the data entry (response rate) for paddy commodities in subround 1 2020 only reached 65,10%, as many as 70,49% of officers still used the measurement and interview method and ther was no difference inthe results of crop cutting survey before the covid-19 pandemic (Subround 1 2019) with the time covid-19 pandemic (subround 1 2020). So it can be concluded that the interview method without measurement can be an alternative because there is no significant difference between the paddy productivity of the measurement method and interviews with the interview without measurement.